A systematic review on the biological evaluation of Calotropis procera (Aiton) Dryand - Abdulrahman Mahmoud Dogara (SpringerOpen, 2023)
Abstract Background Humans have used plants as a safe and effective medicine for a wide range of ailments ever since the earliest days of civilization. Calotropis procera potential as a treatment for a variety of ailments has been known for quite some time. This xerophytic, upright shrub grows to a height of about 6 m and can be found in the tropics of Africa and Asia. Its parts have been used to cure a variety of ailments, including rheumatism, fever, dysentery, diabetes, malaria, asthma, and many more. Here, we provide a synopsis of the available biological data and discuss the possible ways in which Calotropis procera could be used as a novel platform for the treatment of a wide range of diseases. Main body High antioxidant, antiinflammatory, antianalgesic, antimicrobial, antimalaria, antidiabetic, wound-healing, hepato-protective, nerve-recovery, antiulcer, insecticidal, and anticancer effects have been observed in the latex. The research also found that excessive intake has negative health effects. Conclusion The review discovered that the biological evaluation of C. procera in vitro and in vivo animal models was well documented. Human safety and efficacy, however, have yet to be thoroughly tested, and additional well-designed clinical trials are required to confirm preclinical findings. It is essential to establish a standard dose and assure its safety.